(untitled) (Web of Teachers: Inderscience Research, 2026)
Arteries of the 1st and 3rd order belong to the muscular-elastic type, whereas arteries of the 4th–6th order are classified as muscular-type arteries. For a more detailed morphological analysis, the arteries were conditionally divided into three groups: small-, medium-, and large-caliber arteries. The results of our study demonstrated that a well-defined spirally oriented smooth muscle layer develops in the arteries of the 3rd and 4th order. In transverse histological sections, this layer appears as discrete cushion-like thickenings of the vascular wall. It is predominantly located near the external elastic membrane, on the adventitial side. The identified morphological changes indicate structural remodeling of the vascular wall, which is likely associated with impaired microcirculation and chronic metabolic disturbances characteristic of diabetes mellitus. The formation of the spirally arranged smooth muscle layer may represent a compensatory-adaptive mechanism aimed at regulating vascular tone and hemodynamics within the pulmonary circulation.